Cooperative research and development projects: researchers’ motivations for participation and the benefits and barriers they encounter - Carla Fontes; Mario Franco (Asia Pacific Journal of Innovation and Entrepreneurship)
Purpose – Research and development (R&D) initiatives are fundamental for society to evolve in its social, economic, technological and environmental dimensions. This study aimed to provide a view of what motivates researchers to participate in such projects as well as the benefits and barriers they encounter when cooperating in R&D projects. Design/methodology/approach – A qualitative methodology was adopted, within which a case study was conducted: R&D project “GreenHealth - Digital Strategies”. This initiative was based on leveraging biological assets to improve well-being and promote health. Data were obtained from 10 interviews with researchers and documentary analysis such as the project’s official website and social media accounts. Findings – The content analysis led to the conclusion that the researchers’ motivations for participating in R&D projects were the opportunity to contribute to scientific and social evolution, the creation of knowledge and personal factors inherent to the participating researchers. The benefits they derived were related to creating and spreading knowledge, as well as financial incentives. Barriers to participation were related to management, communication, organisational culture, the COVID-19 pandemic. Practical implications – From this study the research team members can understand the importance of cooperation between institutions, which illustrates the importance of creating and transferring knowledge. This study shows also that, in R&D projects, educational and health institutions access new knowledge, attract highly qualified personnel/researchers, establish networks and share financial risks. Originality/value – The study’s innovation derives from its demonstration that an R&D project of this nature is important for several organisations to develop the conception and implementation of a long-term strategy centred on human beings and focused on the eco-sustainability of the affected regions.